Comparison of two regimens of weekly paclitaxel plus gemcitabine in patients with metastatic breast cancer: propensity score–matched analysis of real-world data. (December 2022) - Gong, Chengcheng; Xie, Yizhao; Zhao, Yannan; Li, Yi; Zhang, Jian; Wang, Leiping; Cao, Jun; Tao, Zhonghua; Hu, Xichun; Wang, Biyun
Purpose: Weekly gemcitabine + paclitaxel (wGT) administration is widely applied in real-world clinical practice. The 28-day and 21-day regimens of wGT are the most widely accepted regimens. We evaluated the efficacy and safety of wGT administration in patients with metastatic breast cancer (MBC) and compared the two regimens. Methods: Patients with human epidermal growth factor receptor 2 (HER-2)-negative MBC who received wGT between October 2013 and October 2016 were identified using an electronic database. The outcome variables included progression-free survival (PFS), overall survival (OS), objective response rate (ORR), and safety profile. Propensity score matching was performed to minimize potential confounders. Results: A total of 140 patients were included. The median PFS and OS was 7.8 [95% confidence interval (CI) = 7.0–8.7] months and 22.5 (95% CI = 18.8–26.1) months, respectively. The toxicity of wGT was manageable. Among the patients, 90 (64.3%) received the 21-day regimen and 50 (35.7%) received the 28-day regimen. A higher number of younger patients and patients receiving later-line therapy received the 28-day regimen. There was no significant difference between the two groups in PFS after propensity score matching, though subgroup analysis showed that patients with early relapse benefited more from the 28-day regimen. The ORR was numerically higher in 28-day regimen (37.8% versus 28.0%, p = 0.310). However, the 21-day regimen was better tolerated than the 28-day regimen. Conclusion: wGT administration showed efficacy and safety in patients with MBC. The efficacy was comparable between the two regimens after adjustment for confounding factors while the 21-day regimen was better tolerated. Plain Language Summary: 21-day regimen of wGT was well tolerated in patients with metastatic breast cancer Weekly gemcitabine + paclitaxel (wGT) administration is widely applied in real-world clinical practice. The 28-day and 21-day regimens of wGT are the most widely accepted regimens. We evaluated the efficacy and safety of wGT administration in patients with metastatic breast cancer (MBC) and compared the two regimens. Patients with human epidermal growth factor receptor 2 (HER-2)-negative MBC who received wGT between October 2013 and October 2016 were identified using an electronic database. The outcome variables included progression-free survival (PFS), overall survival (OS), objective response rate (ORR), and safety profile. Propensity score matching was performed to minimize potential confounders. We found that the efficacy was comparable between the two regimens after adjustment for confounding factors while the 21-day regimen was better tolerated.